Sistem Monitoring dan Notifikasi Kualitas Udara Dijalan Raya Dengan Platform IOT - Muhamad Sadali; Yupi Kuspandi Putra; Lalu Kertawijaya; Indra Gunawan (Fakultas Teknik Universitas Hamzanwadi, 2022)
Air pollution and air pollution on the highway is a very bad impact on humans because polluted air can cause various kinds of diseases, therefore in this study, a tool was designed that can be used to monitor air quality over long distances, using Wemos. d1 as a liaison between the MQ-135 sensor with the Internet of Things (IoT) platform and the blynk application which is a monitoring system that if the air quality on the highway where many vehicles pass makes air pollution on the highway less healthy so that it threatens the physical health of living things. One of the efforts to overcome air pollution is by measuring the quality of the air on the highway. connected using the IoT platform as an air quality monitoring system by using the internet as a means of providing information presentation about the air quality on the highway. The results of field testing at 2 points in the East Lombok area found that the quality was still moderate where the air quality was in the range of 400-800. But if the air conditioner is Normal, the range is 0-400 and the last is Abnormal air quality, the range is 800 and above.